Mycetoma: retrospective study of 13 cases in Tunisia - Daoud, Meriem (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Mycetomas are inflammatory pseudotumors of chronic and progressive evolution, of fungal (Eumycetoma), or bacterial (Actinomycetoma) origin. We conducted a retrospective study of patients who have been consulted for mycetoma over a period of 28 years. Thirteen cases of mycetomas were collected during the 28-year period, 10 patients were of rural origin. The lesions were localized on the foot in all instances. There was no male predominance. Histopathological examination confirmed mycetoma in all 13 cases and the determination of the infectious agent in 9 cases: 4 actinomycotic and 5 fungal. Microbiological examination identified the species in 7 cases. Bone involvement was found in 10 cases. Eumycetomas were treated by ketoconazole. The other cases were treated as actinomycetomas by antibiotics. The antibiotictreatment was associated with surgical excision in 4 cases and with amputation in 1 case. Mycetomas are rare in Tunisia, and only observed sporadically, for this reason the diagnosis is usually late, with severe functional, psychological, and socioeconomic consequences.
Keywords: dermatologija; Dermatomikoze; Dermatomycoses; Diagnosis; Maduromikoza; Maduromycosis; mikoze; Retrospective Studies; Retrospektivne študije; Therapy; Tunisia; Tunizija